Health Disparities in Kidney Failure Among Patients With Autosomal Dominant Polycystic Kidney Disease: A Cross-Sectional StudyPlain-Language Summary - Teresa N. Harrison; Qiaoling Chen; Min Young Lee; Mercedes A. Munis; Kerresa Morrissette; Shirin Sundar; Kristin Pareja; Ali Nourbakhsh; Yu-Hsiang Shu; Cynthia J. Willey; John J. Sim, MD (Kidney Medicine, 2023)
Rationale & Objective: Understanding potential differences in patterns of kidney failure among patients with autosomal dominant polycystic kidney disease (ADPKD) may provide insights into improving disease management. We sought to characterize patients with ADPKD and kidney failure across different race/ethnicities. Study Design: Cross-sectional study. Setting & Participants: Kaiser Permanente Southern California members diagnosed with ADPKD between January1, 2002, and December 31, 2018. Exposure: ADPKD. Outcome: Kidney failure, dialysis, or receipt of kidney transplant. Analytical Approach: Differences in characteristics by race/ethnicity were assessed using analysis of variance F test and χ2 test. To compare the range and distribution of the average age at onset of kidney failure by race/ethnicity and sex, we used box plots and confidence intervals. Multivariable logistic regression was used to estimate OR for kidney transplant. Results: Among 3,677 ADPKD patients, 1,027 (27.3%) had kidney failure. The kidney failure cohort was comprised of Black (n=138; 30.7%), White (n=496; 30.6%), Hispanic (n=306; 24.7%), and Asian (n=87; 23.6%) patients. Hispanic patients had the youngest mean age of kidney failure onset (50 years) compared to Black (56 years) and White (57 years) patients. Black (44.2%; OR, 0.72) and Hispanic (49.7%; OR, 0.65) patients had lower rates of kidney transplantation compared to White (53.8%) patients. Preemptive kidney transplantations occurred in 15.0% of patients. Limitations: Retrospective study design and possible misclassification of ADPKD cases. Kidney function calculations were based on equations incorporating race, potentially overestimating kidney function in African Americans. The study was conducted within a single, integrated health care system in 1 geographic region and may not be generalizable to all ADPKD patients. Conclusions: Among a large diverse ADPKD population, we observed racial/ethnic differences in rates of kidney failure, age of kidney failure onset, and rates of kidney transplantation. Our real-world ADPKD cohort provides insight into racial/ethnic variation in clinical features of disease and potential disparities in care, which may affect ADPKD outcomes.